Neuroretinal degeneration in a mouse model of systemic chronic immune activation observed by proteomics - Khan, Asif Manzoor; Steffensen, Maria Abildgaard; Paskeviciute, Egle; Abduljabar, Ahmed Basim; Sørensen, Torben Lykke; Vorum, Henrik; Nissen, Mogens Holst; Honoré, Bent (Frontiers in Immunology, 2024)
Blindness or vision loss due to neuroretinal and photoreceptor degeneration affects millions of individuals worldwide. In numerous neurodegenerative diseases, including age-related macular degeneration, dysregulated immune response-mediated retinal degeneration has been found to play a critical role in the disease pathogenesis. To better understand the pathogenic mechanisms underlying the retinal degeneration, we used a mouse model of systemic immune activation where we infected mice with lymphocytic choriomeningitis virus (LCMV) clone 13. Here, we evaluated the effects of LCMV infection and present a comprehensive discovery-based proteomic investigation using tandem mass tag (TMT) labeling and high-resolution liquid chromatography–tandem mass spectrometry (LC-MS/MS). Changes in protein regulation in the posterior part of the eye, neuroretina, and RPE/choroid were compared to those in the spleen as a secondary lymphoid organ and to the kidney as a non-lymphoid but encapsulated organ at 1, 8, and 28 weeks of infection. Using bioinformatic tools, we found several proteins responsible for maintaining normal tissue homeostasis to be differentially regulated in the neuroretina and the RPE/choroid during the degenerative process. Additionally, in the organs we observed, several important protein pathways contributing to cellular homeostasis and tissue development were perturbed and associated with LCMV-mediated inflammation, promoting disease progression. Our findings suggest that the response to a systemic chronic infection differs between the neuroretina and the RPE/choroid, and the processes induced by chronic systemic infection in the RPE/choroid are not unlike those induced in non-immune-privileged organs such as the kidney and spleen. Overall, our data provide detailed insight into several molecular mechanisms of neuroretinal degeneration and highlight various novel protein pathways that further suggest that the posterior part of the eye is not an isolated immunological entity despite the existence of neuroretinal immune privilege.